The assessment of HER2 status in breast cancer: the past, the present, and the future. Issue 6 (7th April 2016) - Nitta, Hiroaki; Kelly, Brian D.; Allred, Craig; Jewell, Suzan; Banks, Peter; Dennis, Eslie; Grogan, Thomas M.
Abstract : Humanized monoclonal anti‐human growth factor receptor 2 (HER2) antibody trastuzumab was approved for HER2 positive breast cancer patient treatment 11 years after the demonstration of HER2 gene amplification associated with the HER2 protein overexpression in breast cancer in 1987. HER2 positive status of breast cancer patients is assessed by HER2 gene amplification with in situ hybridization (ISH) and/or HER2 protein overexpression with immunohistochemistry (IHC). Because the discordance between quantitative HER2 ISH and subjective, semi‐quantitative HER2 IHC assay results is a well‐recognized issue of HER2 testing, we developed an assay combining HER2 ISH and HER2 IHC assays (HER2 gene‐protein assay; HER2 GPA) as one test on the same tissue section. HER2 GPA allows pathologists to score the HER2 gene and HER2 protein status simultaneously at the individual cell level. The possibility that HER2 GPA may become the next generation of HER2 testing is discussed, particularly for cases in which it is difficult to assess the HER2 status of breast cancer patients due to the HER2 heterogeneity.